Design Of Steel Structures. - S, Sai Ram K. (2010)
This book on Design of Steel Structures uses Limit State Method and follows the latest BIS Codes, BIS: 800: 2007.A perfect mix of concise theory with relevant applications and inclusion of most recent design methodologies makes this an excellent offering to students and practicing engineers.
7.4 Design of End Panels as per IS 800:2007 -- 7.5 Other Design Specifications -- 7.6 Design of Stiffeners -- Problems -- CHAPTER 8 BEAM-COLUMNS -- 8.1 Introduction -- 8.2 Analysis of Beam-columns -- 8.3 Modes of Failure -- 8.4 Design Specifications as per IS 800:2007 -- Problems -- CHAPTER 9 COLUMN SPLICES AND BASES -- 9.1 Introduction -- 9.2 Column Splices -- 9.3 Column Bases -- Problems -- CHAPTER 10 WELDED CONNECTIONS -- 10.1 Introduction -- 10.2 Bracket Connections -- 10.3 Simple Beam End Connections -- 10.4 Moment Resistant Beam End Connection -- Problems -- CHAPTER 11 BOLTED CONNECTIONS -- 11.1 Introduction -- 11.2 Bracket Connections -- 11.3 Simple Beam End Connections -- 11.4 Moment Resistant Beam End Connection -- 11.5 Splicing of Beams/Plate Girders -- Problems -- CHAPTER 12 LIGHT-GAUGE STEEL SECTIONS -- 12.1 Introduction -- 12.2 Types of Sections -- 12.3 Behaviour of Light-gauge Sections -- 12.4 Design Specifications as per IS 801:1975 -- Problems -- CHAPTER 13 COMPOSITE CONSTRUCTION -- 13.1 Introduction -- 13.2 Composite Beam -- 13.3 Methods of Construction -- 13.4 Limit State of Collapse -- 13.5 Limit States of Serviceability: Deflection -- Problems -- APPENDICES -- Appendix A: Properties of Beams, Columns/Heavy Beams, Channels and Angles -- Appendix B: Properties of Parallel Beams and Columns -- Appendix C: Properties of T-Sections -- Appendix D: Properties of Tubular Sections -- Appendix E: Properties of Rectangular/Square Hollow Sections -- Appendix F: Properties of Flats -- Appendix G: Properties of Cold-formed Light-gauge Sections -- REFERENCES -- INDEX.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books